Design of the competitive advantage & strategic plan for the microenterprise chepas Franciscanas in Bolívar-Colombia (2021)
This article presents a proposal for the competitive advantage and strategic plan to boost the growth of the microenterprise Chepas Franciscanas S.A.S, located in Carmen de Bolívar, this was carried out on the basis of descriptive research, through a qualitative approach combining induction and analysis methods. Instruments such as nonparticipating direct observation, internal, external factor workshops, values and principles, virtual interviews, tools such as SWOT, POAM and PCI analysis, Porter's 5 forces, strategic map and Balanced Scorecard tool were used to obtain the required information.